KARAKTERISTIK DAN TINGKAT KOMPETENSI PENYULUH PERTANIAN SWADAYA DI KABUPATEN TANAH DATAR (Characteristic Profile And Competency Level Of Independent Agricultural Extension Workers In Tanah Datar Regency) - YUZINOSFRIS, YUZINOSFRIS; SYAHNI, RAHMAT; ASMAWI, ASMAWI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2025)
This study aims to analyze the characteristics and competence levels of Independent Agricultural Extension Workers (IAEW) in Tanah Datar Regency. The research employed a descriptive quantitative method with a survey approach involving 85 respondents selected through a census technique. Data were collected using questionnaires and interviews, then analyzed using frequency and percentage tabulations. The findings show that most IAEWs are aged ≥50 years (62.81%), have a senior high school education (56.4%), and possess 4–6 years of extension experience (35.9%). Psychologically, the majority demonstrate high motivation (52.6%), broad cosmopolitan orientation (46.1%), and strong creativity and innovation (50%). Overall, the IAEW competence level falls into the moderate category (61.53%), followed by low (21.80%) and high (16.67%). The technical dimension shows the highest competence, while managerial, institutional, coordination, and collaboration aspects need further strengthening. These results highlight the importance of continuous managerial and institutional capacity-building programs to enhance the role of IAEWs as strategic partners of government extension workers in promoting sustainable agricultural development.